A closer look at right ventricular 3D volume quantification by transthoracic echocardiography and cardiac MRI. Issue 6 (June 2019) - Greiner, S.; André, F.; Heimisch, M.; Aurich, M.; Steen, H.; Katus, H.A.; Mereles, D.
Abstract : AIM: To compare right ventricular (RV) volumetry using state-of-the-art three-dimensional (3D) transthoracic echocardiography (3DE) and cardiac magnetic resonance imaging (CMR) near-simultaneously in a clinical setting. MATERIALS AND METHODS: Forty-seven consecutive patients received comprehensive echocardiography including 3DE within 30 minutes of CMR. RV volumetry was performed offline with semi-automated 3D endocardial border tracing as well as manual delineation of the compacted myocardium in short-axis views by CMR. RESULTS: Forty-two examinations (89%) could be analysed offline by 3D RV reconstruction. Mean RV volumes assessed by CMR and 3DE were 215±63 and 127±42 ml for end-diastole (RV-EDV), as well as 110±43 and 62±27 ml for end-systole (RV-ESV). RV-EDV, RV-ESV, and RV stroke volume measured by 3DE were significantly lower than RV volumetry by CMR. Mean bias were –88, –48, and –41 ml, respectively. Mean RV ejection fraction (-EF) showed a non-significant deviation of +2% between 3DE and CMR and the correlation coefficient was r= 0.58 for RV-EF. CONCLUSION: RV-EF can be assessed reliably using transthoracic 3DE in patients with good image quality; however, absolute RV volumes measured by 3DE show a systematic deviation to CMR volumetry that has been previously neglected and requires careful interpretation regarding anatomical cardiac imaging. Highlights: Near-simultaneous image acquisition by CMR and 3DE in 47 patients. Detailed statistical work-up of absolute RV measurements and derived parameters like RV-EF. Comparison and discussion in regard to the results of former studies.